Comparison of the Efficacy of 5% Dapsone Gel and 1% Clindamycin Phosphate Gel in the Treatment of Mild to Moderate Acne Vulgaris - Iftikhar, Arooba; Naima Luqman; Sara Mubeen; Maryam Tariq; Humna Khalid; Komal Naseer (Journal of Pakistan Association of Dermatologists, 2025)
Introduction: Acne vulgaris, a chronic dermatological condition, is characterized by hair follicle blockage by dead skin cells and sebum, leading to various manifestations including blackheads, whiteheads, and possible scarring. This study aimed to evaluate dapsone gel's effectiveness and safety in treating acne vulgaris compared to clindamycin gel, offering insights for managing this prevalent skin condition. Objective: To compare the efficacy of 5% dapsone gel and 1% clindamycin phosphate gel in the treatment of mild to moderate acne vulgaris. Methods: A randomized clinical trial at Bahawal Victoria Hospital focused on treating mild to moderate acne vulgaris from February to August 2023. 110 patients were recruited, with 55 in Group-I receiving dapsone gel and 55 in Group-II receiving Clindamycin gel. The 3-month treatment aimed at assessing efficacy and safety for moderate acne vulgaris management, offering insights for healthcare professionals. Results: In group-A (5% Dapsone gel), 43(78.2%) had efficacy, while in group-B (1% Clindamycin gel), 29(52.7%) had efficacy with a p-value 0.005, which is statistically significant. Conclusion: Dapsone 5% gel monotherapy demonstrated superior efficacy outcomes in comparison to the clindamycin phosphate 1% gel monotherapy following a 12-week treatment period, offering the added benefit of a simplified treatment regimen through its once-daily topical administration.